Design Development of On-Board DC Fast Chargers for E-Rickshaw - DIxit A.; Pande K.; Rathore A.K.; Singh R.K.; Mishra S.K. (My University, 2025)
This paper proposes a single-phase 3.3 kW onboard battery charger for E-Rickshaw with a Single-stage Active Power Factor Correction (PFC) Buck-Boost Converter topology. Normally, E-Rickshaw battery charger is heavy and bulky in dimensions and comprises of a power-factor corrector (PFC) and a DC-DC converter. A traditional single-phase PFC converter has three sensors namely input voltage, input current, and output voltage for measurement. The proposed converter is more compact and more flexible in terms of control and conversion stages a with new Unity Power Factor alongside a combination of a full-bridge diode rectifier and a single switch Buck-Boost converter by just using one output voltage sensor is presented. The suggested control technique uses only one integrator to compensate for the steady-state error and is very simple to implement. The proposed battery charger accomplish Unity Power Factor at variable AC input with a small inductance. To verify the feasibility of the proposed scheme, the proposed battery charger topology is simulated in PSIM. The simulation result indicates a 95% peak efficiency at 220Vac and 93% at a variable input voltage from 170V-280V at 3.3kW. A scaled-down lab prototype of 1.5kW is built and experimental results are presented to verify the suitability of the proposed converter. © 2019 IEEE.